Media In Ã¢â‚¬Å“Gerakan Cikapundung BersihÃ¢â‚¬Â - Octavianti, Meria; Mulyana, Slamet (Forum Ilmu Sosial, 2017)
ikapundung is the river that divides Bandung which provide aesthetics function as well as maintain city's stability. This supposedly clean and well-kept river is in fact very dirty and filled with various waste. The accumulation of waste in Cikapundung River resulting siltation threaten the balance of the ecosystems. Flood and waste will be the main problem of the city if this poor situation cannot be overcome. Therefore, the Government has included the river in their priority program of the development plan. The rehabilitation of the river has been proclaimed through Gerakan Cikapundung Bersih (Clean Cikapundung River Movement). As an campaign event, the messages from Gerakan Cikapundung Bersih must be delivered to the audience effectively. Considering this, by using case study descriptive approach, this research sought to reveal the various types of campaign media used in Gerakan Cikapundung Bersih. Data were collected from interviews, observations and literature study. The results showed that media used in Gerakan Cikapundung Bersih are outdoor and alternative media. However, the most effective way to deliver campaign messages is direct communication (interpersonal), especially by Kuya Gaya 15 community through their activities such as kukuyaan and gotong royong. Word of mouth (interpersonal communication) is the method which drive of the success of the campaign.